Regulatory Role of rno-miR-30b-5p in IL-10 and Toll-like Receptor 4 Expressions of T Lymphocytes in Experimental Autoimmune Uveitis In Vitro. (29th October 2018) - Sun, Yuanyuan; Guo, Dadong; Liu, Bin; Yin, Xuewei; Wei, Huixia; Tang, Kai; Bi, Hongsheng
Abstract : Uveitis is a serious eye disease that usually damages young adult's health. MicroRNAs (miRNAs) are a class of small noncoding RNAs which regulate messenger RNA (mRNA) expression. It is predicted that rno-miR-30b-5p can regulate the expressions of interleukin-10 (IL-10) and Toll-like receptor 4 (TLR4). In this study, the regulatory role of rno-miR-30b-5p in IL-10 and TLR4 gene expressions was validated using luciferase activity assay. Further, the inflammatory manifestation of the anterior segment and pathological examination of the eye were explored in experimental autoimmune uveitis (EAU) rats. Meanwhile, the levels of rno-miR-30b-5p in eye tissues, spleen, and lymph nodes were measured using quantitative PCR (Q-PCR). IL-10 and TLR4 in spleen and lymph nodes were further separately determined by using Q-PCR and Enzyme-Linked Immunosorbent Assay (ELISA). Moreover, rno-miR-30b-5p mimic and its inhibitor were separately transfected into purified T cells, and the levels of IL-10 and TLR4 were detected using PCR, flow cytometry, and ELISA techniques. Results indicate that rno-miR-30b-5p was downregulated in spleen, lymph nodes, and eye tissues whereas the expressions of IL-10 and TLR4 at mRNA and protein levels were upregulated. The levels of IL-10 and TLR4 were negatively correlated to rno-miR-30b-5p levels. The result of in vitro cell transfection experiment indicates that IL-10 and TLR4 expressions were inhibited at mRNA and protein levels after T cells incubated with rno-miR-30b-5p mimic. However, the IL-10 and TLR4 mRNA levels were upregulated in purified T cells from spleen and lymph nodes after treatment with miR-30b-5p antagonist. In addition, there was no evident change of IL-10 and TLR4 proteins in spleen and lymph node T cells between EAU control and negative treatment groups. Flow cytometry analysis revealed that rno-miR-30b-5p mimic could reduce the number of both IL-10 and TLR4 positive cells, whereas rno-miR-30b-5p inhibitor could increase the number of IL-10 and TLR4 positive cells. Our study demonstrates that rno-miR-30b-5p influences the development of uveitis by regulating the level of IL-10 and TLR4 positive cells, thereby playing a role in the pathogenesis of uveitis.